Ein Sprengkopf denkt nichts - Schwalme, Reine (Staatlicher Kunsthandel der DDR, 1984)
A superhero with dollar sign on chest, USA flag for cloak, and warhead for head Suggested translation: A warhead thinks nothing PO-1879